Muko · kaiko, relectura de K.9.1 (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this article it is to propose a new reading of K.9.1, a Celtiberian inscription inscribed on a small sheet of bronze from Peña Redonda. It has traditionally been read as an only word: mukokaiko, but we have detected an interpuncture that divides it in two: muko·kaiko.